Assessing the health status of trees in UNIMAS for sustainable urban landscape - Heida, bt Mohamad Kamel (Universiti Malaysia Sarawak (UNIMAS), 2015)
rhe existence of urban forests in the city plays an important role in providing numerous environmental, social and economic benefits to the people. Urban forests not only create an escape for the city dwellers from their hectic everyday life, it also helps to improve water and air quality, reducing flood, reducing heating and cooling energy needs, increasing the value of the property and enhancing the quality of life for people and wildlife around the~) The main objective of this study was to assess and evaluate the health status of the selected trees species planted within Universiti Malaysia Sarawak (UNIMAS). A total of 328 trees from the species of R. regia. A. heterophylla and Y. aloifolia were assessed for their overall health status. The characteristics of the tree species planted and methods to improve their health problems were discussed so as to attain sustainable urban landscape.